A Combined Approach To Crooked Nose Deformity - BİNNETOĞLU, ADEM; İNANLI, SELÇUK (SPRINGER, 2016)
Crooked nose deformity is a complex anatomical deformity; therefore, repair remains a challenge. Here, we introduce a new technique for crooked nose deformity repair. Twenty-two patients underwent intraoperative evaluations and measurements, followed by surgery using the open rhinoplasty technique. Our method involves three major steps. First is the creation of an asymmetric medial oblique osteotomy using piezoelectric ultrasonic surgery and double lateral osteotomies, wherein the asymmetric bony ascending part of the maxillary bone at the base of the nasal vault is fractured, pushed in, and delivered to the face. Second is septoplasty with L-strut preservation. The L-strut is removed as a 1-cm block caudally from the septal stump of the keystone area. A (or double) fabricated batten cartilage graft is placed on the concave side of the deviation and sutured to cover the septal stump. The L-strut is then replaced and sutured on the batten graft, redirecting the septum toward the midline. Third is an overlapping cruroplasty on the side of the long asymmetrical lower lateral cartilage to equalize both wings and correct tip deviation. Our new technique was effective for the treatment of crooked nose deformity. Our technique of K-stone batten plasty with delivery to the face and overlapping cruroplasty may be an effective surgical method for crooked nose deformity. This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Crooked nose; Twisted nose; Rhinoplasty; Extracorporeal septoplasty; DEVIATED NOSE; NASAL; RECONSTRUCTION; GRAFT